Bateria Montreal-Toulouse de avaliação da linguagem -versão breve: estudos psicométricos - Altmann, Raira Fernanda (2023)
This study aimed to seek psychometric evidence of validity and reliability for the MTL-BR Brief Battery and to verify the sensitivity and specificity, and to present the cut-off points for this instrument tasks. Construct validity was verified by convergent validity, with 46 (30 neurologically healthy adults and 16 with aphasia). For criterion validity, the Holm-Bonferroni method was used, presenting a total of 110 participants (73 neurologically healthy adults and 37 with aphasia). Regarding reliability, this was evaluated by the inter-rater agreement, through the analysis of Intraclass Correlation Coefficient, with a sample of 30 participants with aphasia. For the test-retest reliability study, the sample consisted of 15 participants with aphasia, and the analysis was performed by the Intraclass Correlation Coefficient. For internal consistency, Cronbach’s alpha was used, containing a sample of 37 participants with aphasia. To verify the diagnostic accuracy of the instrument, sensitivity and specificity were used using the ROC curve, from a sample of 223 participants (192 neurologically healthy adults and 31 with aphasia). The present study showed satisfactory psychometric evidence related to criterion and construct validity, inter-rater reliability, test-retest and internal consistency, as well as sensitivity and specificity, and cutoff point for the MTL-BR Brief Battery.